Profesionalitas Aparatur Sekretariat Daerah di Kabupaten Sumbawa Besar - JUANDA, KHAIRY (Jurnal Studi Pemerintahan, 2010)
The aim of this research is knowing the profesionality of aparature at local secretary of Sumbawaregion in doing their work depend on function and job description. Beside that, this research try toknow some obstacles and find the solution to increase aparature profesionality at Sekretariat DaerahKabupaten Sumbawa. This reseach's title is a Profesionality of aparature at local secretary ofSumbawa region. Research methods is used descriptive survey, documentation, Questioner, interview.The respondents of this research are civil servant at Sekretariat Daerah Kabupaten Sumbawa. Fromthis research knew that civil servant competency is good, Acuntability is good, Recruitment is fair,Education level is poor. The conclution is aparature's profesionality at local secretary of Sumbawaregion in fair level.